Decreasing Dissemination of Disturbances within Network Systems by Neural Networks - Olga V. Fridman; Alexander Ya. Fridman (Institute of Advanced Engineering and Science, 2013)
We apply neural networks to locate initial sources of disturbances in network systems during coordinating them by a gradient coordination technique based on the earlier proposed necessary and sufficient coordinability conditions for locally organized hierarchies of dynamic systems. Thus we restrict spread of disturbances and save resources spent for maintaining of the system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2903